2020
DOI: 10.3390/ma13061477
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Filler Loading on the Mechanical Properties of Flowable Resin Composites

Abstract: The aim of this study was to evaluate the correlation between the percent of inorganic filler by weight (wt. %) and by volume (vol. %) of 11 flowable resin composites (FRCs) and their mechanical properties. To establish the correlation, the quantity of inorganic filler was determined by combustion and shape/size analyzed by SEM images. The compressive strength (CS), flexural strength (FS), and flexural modulus (FM) were determined. The CS values were between 182.87-310.38 MPa, the FS values ranged between 59.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 32 publications
2
28
0
4
Order By: Relevance
“…Despite the differences in the structure of materials, a high positive correlation (R = 0.822) was observed between the filler content (by volume) and the microhardness. A similar relationship was observed by Ling et al [ 39 ], Chung (R = 0.89) [ 40 ] and Mirica et al [ 44 ]. The hardness of the material can also be related to the abrasion and materials with low hardness may be more susceptible to wear [ 46 ].…”
Section: Discussionsupporting
confidence: 88%
“…Despite the differences in the structure of materials, a high positive correlation (R = 0.822) was observed between the filler content (by volume) and the microhardness. A similar relationship was observed by Ling et al [ 39 ], Chung (R = 0.89) [ 40 ] and Mirica et al [ 44 ]. The hardness of the material can also be related to the abrasion and materials with low hardness may be more susceptible to wear [ 46 ].…”
Section: Discussionsupporting
confidence: 88%
“…A higher weight fraction of glass filler particles would result in higher light scatter causing a decrease in total energy received and thus causing insufficient polymerisation of the monomer. In this study, the individual particle volumes of filler, 50AR and 70AR fibres were 0.14, 4909.00 and 6872.00 mm 3 , respectively. Hence, the number of particles was reduced by replacing 5 wt% fillers with 5 wt% long fibres and additionally the glass fibres transmit light through its length in different directions when randomly oriented, causing higher light penetration through the thickness, resulting in a degree of conversion, and curing depth.…”
Section: Discussionmentioning
confidence: 61%
“…Filler is an important factor that can significantly affect the mechanical strength of composite materials [ 4 ]. In another study by Mirica et al [ 71 ], it was reported that the flexural strength can be improved to 60–90 MPa with the addition of around 50% appropriate fillers. At the same study [ 71 ], the prepared flowable composite had compressive strength of 182–310 MPa and flexural modules of 2.34–6.32 GPa, which was higher than those of the conventional flowable composites owing to the selection of functional fillers.…”
Section: Dental Filling Compositementioning
confidence: 99%